2022
DOI: 10.24298/hedn.2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disaster prevention awareness and preparedness among residents living in mountainous areas of Japan

Abstract: Aim: This study aimed to clarify the factors influencing disaster prevention awareness and their association with disaster preparedness among residents living in mountainous areas of Japan. Methods: An anonymous self-administered questionnaire survey was conducted with health examination participants in City A in August 2018. The survey items included basic attributes, disaster prevention awareness and related factors, and disaster preparedness. Descriptive statistics were performed on each item, followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…This study found no significant difference in disaster prevention consciousness scores; however, significant differences were observed on the "Sense of Crisis for Current Situation" scores before and after the public lecture. A national survey of adult men and women in Japan previously reported a Disaster Prevention Consciousness score of 73.3 (Shimazaki & Ozeki, 2022, Tada, Iwamoto, Kubo, & Senou, 2022, whereas the average score in this study was 81.7. Our current findings suggest that an education method centered on lectures did not further improve the participants' disaster awareness, as they already had a high level of disaster prevention awareness before attending the public lecture.…”
Section: Changes In Disaster Prevention Consciousness After the Lecturecontrasting
confidence: 77%
“…This study found no significant difference in disaster prevention consciousness scores; however, significant differences were observed on the "Sense of Crisis for Current Situation" scores before and after the public lecture. A national survey of adult men and women in Japan previously reported a Disaster Prevention Consciousness score of 73.3 (Shimazaki & Ozeki, 2022, Tada, Iwamoto, Kubo, & Senou, 2022, whereas the average score in this study was 81.7. Our current findings suggest that an education method centered on lectures did not further improve the participants' disaster awareness, as they already had a high level of disaster prevention awareness before attending the public lecture.…”
Section: Changes In Disaster Prevention Consciousness After the Lecturecontrasting
confidence: 77%
“…A study in South of Zambales, Philippines in 2020 showed that there is a significant link between awareness and disaster preparedness among local communities ( 23 ) The linear relationship of disaster awareness and preparedness was also found by Suryaratri et al (2020) which stated that the higher public awareness of disasters, the higher the preparedness for disasters ( 17 ) The study even found that 50.5% of household preparedness in the in Banten Sub-District, Indonesia is determined from its awareness of disasters. Similar finding conveyed by Tada et al (2021) who through a survey proved that people who are declared ready for disasters have a high score on the disaster prevention awareness scale ( 31 ) A study in the Philippines even highlighted that it is necessary to increase public awareness and knowledge about potential disasters even in communities that have a relatively lower risk ( 32 ).…”
Section: Discussionsupporting
confidence: 56%
“…To promote teacher education on disaster prevention, it is necessary to raise awareness of disasters and to identify factors that may promote it. Disaster prevention awareness is defined as the degree to which an individual is aware on a daily basis that information, materials, and social preparation for disasters are necessary [30,35]. In this study, we used a scale with five scores: imagination of the disaster situation, sense of crisis, being other oriented, interest in disasters, and anxiety.…”
Section: Discussionmentioning
confidence: 99%